Perjalanan Old Public Administration (OPA), New Public Management (NPM), New Public Service (NPS) Menuju Manajemen Publik Kelas Dunia - Jamaluddin Ahmad (PRAJA: Jurnal Ilmiah Pemerintahan, 2029)
Abstract This article works through about how Old Public Administration's trip, New Public Management, and New Public Service to become world class Public Management. The ideas of this concept then were criticized by NPM, and the NPM were counter-criticized by NPS. Besides, this article will also works through several explanations about the comparation among OPA, NPM, and NPS which were made Indonesian perspective base to become world class Public Management. Keywords: Old Public Administration, New Public Management, New Public Service